2005
DOI: 10.1177/107769900508200405
|View full text |Cite
|
Sign up to set email alerts
|

How Newspaper Sources Trigger Gender Stereotypes

Abstract: News stories rely on sources to convey information. Official sources are often titled and typically male. This study outlines how such source cues can trigger gender stereotypes to varying degrees in two experimental studies. When the unofficial source cue offered ambiguous gender information, individual differences in propensity to stereotype were shown. Those people who score high on an ethic of caring were less likely to attribute a gender to the source. Results are explained in terms of processing differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
2
30
1
2
Order By: Relevance
“…The results of H3 were unexpected and conflicted with literature on gender and sources as well as sexuality and sources (Armstrong 2004;Armstrong and Nelson 2005;Freedman and Fico 2005;Gross 2001;Sender 2001;Tuchman 1978;Zoch and VanSlyke Turk 1998). Delving deeper into the data revealed that gay male sources and lesbian sources were distributed differently in the four newspapers.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…The results of H3 were unexpected and conflicted with literature on gender and sources as well as sexuality and sources (Armstrong 2004;Armstrong and Nelson 2005;Freedman and Fico 2005;Gross 2001;Sender 2001;Tuchman 1978;Zoch and VanSlyke Turk 1998). Delving deeper into the data revealed that gay male sources and lesbian sources were distributed differently in the four newspapers.…”
Section: Resultscontrasting
confidence: 74%
“…Reflecting previous research on gender in newspapers (Armstrong 2004;Armstrong and Nelson 2005;Freedman and Fico 2005;Tuchman 1978;Zoch and VanSlyke Turk 1998), hypothesis one predicts that articles about same-sex marriage will contain significantly more male sources than female sources. Additionally, hypothesis two predicts that articles about same-sex marriage will contain significantly more male official sources than female official sources.…”
Section: Gender and Newspapersmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research in other national contexts has repeatedly found that men are more likely than women to be used as expert sources in newspapers (Armstrong and Nelson 2006;Zoch and VanSlyke Turk 1998) and on television, particularly for stories involving "hard news" topics such as politics (Cann and Mohr 2001;Desmond and Danilewicz 2010). When women do appear as sources on television news, it tends to be in connection with "softer" topics, such as health or lifestyle, and they often are represented in a "ritualized" way, offering a "contained and safe" representation of how actions taken in the public sphere affect those in the private sphere (Rakow and Kranich 1991, 16).…”
Section: Literature: News Sourcesmentioning
confidence: 99%
“…En estos trabajos, normalmente basados en el análisis del producto informativo, se incide en la invisibilización de las mujeres en los medios (Len-Rios et al, 2005), la divulgación de estereotipos de género cuando se informa de ellas (Mateos de Cabo, 2007;Armstrong y Nelson, 2005) y el uso de un lenguaje sexista (Bach et al, 2000). Por otro lado, y desde la perspectiva más empresarial, se pone de manifiesto el escaso interés que las mujeres muestran por la lectura de prensa general de pago (el caso de la prensa especializada, económica y deportiva, todavía es más extremo), centrándose en que el producto informativo no responde en contenidos o enfoques a las necesidades informativas que ellas tienen.…”
Section: Investigación Sobre Mujeres Y Medios De Comunicaciónunclassified